(3MGTjI Ydi TQM GdSeQbfOjIs - (3CMeO Hf MjOQ Hf CMeO GdcQOi GdMSjfj BHGOis; (3GdYUGe GdGSaQGjjfj , YUGe GdOjf EHQGgje Hf eMeO Hf YQH TGg GdESaQGjjfj, GdYUGe GdESaQGjjfj,J (B945 (3g` s ((3Ydi Hf YHO Gddg s)
(3ChdgG (B:s
(3CeG HYO ajbhd CabQ GdNdb deG cGf GdTQM GdefShH Hf YQHTGg Ydi GdQSGdI GdeUfaI ai GdGSJYGQGJ s
(3BNQgG (B:s
(3KHhJ GdJLQjO dgG bhdg GdCXgQ hLg s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdfSNI HgG MhGTs
(3hQO GdYfhGf GdCUdi ai cX (B1/ 853s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdHdGZIs